2021
DOI: 10.14411/fp.2021.001
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of the Coccidia (Apicomplexa: Conoidasida) in vertebrates: what we know, what we do not know, and what needs to be done

Abstract: Over the last two decades my colleagues and I have assembled the literature on a good percentage of most of the coccidians (Conoidasida) known, to date, to parasitise: Amphibia, four major lineages of Reptilia (Amphisbaenia, Chelonia, Crocodylia, Serpentes), and seven major orders in the Mammalia (Carnivora, Chiroptera, Lagomorpha, Insectivora, Marsupialia, Primates, Scandentia). These vertebrates, combined, comprise about 15,225 species; only about 899 (5.8%) of them have been surveyed for coccidia and 1,946 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 129 publications
0
11
0
Order By: Relevance
“…As a case in point, there are ~8120 extant species of amphibians on Earth (Frost, 2020), but only 45 amphibian species (0.5%) have been examined for apicomplexans and from them, 52 apicomplexan species and 38 other forms ( species incertae sedis , species inquirendae , etc.) have been documented in the literature ( Duszynski et al, 2007 ; Duszynski, 2021 ). Unfortunately, this demonstrates that our knowledge of apicomplexan species richness is based on very limited, non-exhaustive sampling, which does not allow estimates for species richness at any scale.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As a case in point, there are ~8120 extant species of amphibians on Earth (Frost, 2020), but only 45 amphibian species (0.5%) have been examined for apicomplexans and from them, 52 apicomplexan species and 38 other forms ( species incertae sedis , species inquirendae , etc.) have been documented in the literature ( Duszynski et al, 2007 ; Duszynski, 2021 ). Unfortunately, this demonstrates that our knowledge of apicomplexan species richness is based on very limited, non-exhaustive sampling, which does not allow estimates for species richness at any scale.…”
Section: Introductionmentioning
confidence: 96%
“…Currently, it includes four subfamilies: Sarcocystinae Poche, 1913 ( Sarcocystis, Flenkelia ), Toxoplasmatinae Biocca, 1957 ( Toxoplasma, Hammondia, Heydornia, Neospora , Besnoitia ), Cystoisosporinae Frenkel et al, 1987 ( Cystoisospora ), and Eumonosporinae Chou et al, 2021 ( Eumonospora ), along with the genera Hyaloklossia and Nephroisospora ( Frenkel et al, 1979 ; Smith, 1981 ; Sercundes et al, 2016 ; Duszynski et al, 2018 ; Chou et al, 2020 ; Chou et al, 2021 ). Hyaloklossia is a monotypic genus that is clearly distinguishable from other genera of Sarcocystidae based on its homoxenous (direct) life cycle, gametogony and sporogony in frog renal tissues, and unusual oocyst morphology ( Modrý et al, 2001 ; Duszynski et al, 2007 ; Duszynski, 2021 ). Based on these observations, Hyaloklossia is an independent lineage from other members of the Sarcocystidae ( Modrý et al, 2001 ; Šlapeta et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although Eimeria species were described morphologically from insectivorous mammals [ 51 ], molecular data are scarce. Cross-infection studies have shown that coccidia from one host family generally do not infect hosts from other families or orders, although some coccidia are less host specific [ 51 , 52 , 53 ]. Therefore, considering the high prevalence of Eimeria in our study, we plan on untangling the true diversity of Eimeria spp.…”
Section: Discussionmentioning
confidence: 99%
“…For over 120 years, the genus was considered monotypic: containing only a single species, H. lieberkuehni ( Labbé, 1894 ), reported from Pelophylax spp. (Anura: Ranidae) in Europe ( Modrý et al, 2001 ; Duszynski et al, 2007 ; Duszynski, 2021 ). Recently, a second species, Hyaloklossia kasumiensis Tokiwa, Chou, Tochigi, Katayama et Duszynski, 2021 , was described from Japan in East Asia ( Tokiwa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%